Analisa Pengendalian Kualitas Produk HUBAB di PT. Dalwa Anugrah Hasaniyah Menggunakan Metode Six Sigma - Takwah, Khoiruz Zadit (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the quality control of HUBAB brand bottled drinking water (AMDK) produced by PT. Dalwa Anugrah Hasaniyah using the Six Sigma method. Data were collected through observation, interviews, and literature studies of production data and defective products during December 2024 to January 2025. Based on the results of the analysis, the average value of Defects Per Million Opportunities (DPMO) was 1813.06 with a sigma level of 4.44. The most common types of defects include damage to the lid and cup leakage. The main factors causing lid damage include inadequate raw material quality, excessively high press machine temperatures, and worker carelessness. Meanwhile, the cause of cup leakage is due to the accumulation of raw materials exceeding the maximum limit, storage for too long, and operator negligence.